Stanowisko Parlamentu Europejskiego wobec Partnerstwa Wschodniego - Staszczyk, Artur (Rocznik Integracji Europejskiej, 2015)
This paper presents the attitude of the European Parliament to those issues that fall within the scope of interest of the Eastern Partnership. In the analysis of this attitude, the author stresses the significant role the EP has played in developing EU Eastern policy, in particular as concerns the promotion of democratic ideas and values within the scope of this policy. It should be emphasised that the EP is exceptionally interested in the advancement of democracy in East European partner countries, whose geopolitical significance the EP appreciates, frequently calling for the tightening of relations with these countries, and even opening European prospects to them. The deepening of cooperation between the EU and East European countries is conditioned by the EP by their adoption of what is called European values (i.e. democracy, rule of law, protection of human rights, etc.). Acting as the ‘guard of democracy,’ the EP is an institution of political influence which allows it to shape Eastern policy in ways that go beyond the formal rights vested in it by the treaties.